Numerical investigation on lateral deflection of single pile under static and dynamic loading - Rahemi, Negar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2012)
ABSTRACT: In this thesis a 3D nonlinear analysis was performed to study the lateral deflection of single pile with different slenderness ratios (L/D) under static and dynamic loading. Different models of pile, soil and loading have been simulated, and the lateral deflections were studied considering elastic, elasto-plastic and dynamic models of the soil. For seismic load modeling Ricker wavelet was used. 3D finite element method was applied for numerical modeling and the ABAQUS program version 6.11was utilized to evaluate the lateral deflection of pile. It was concluded that one of the most effective parameters on lateral deflection of pile is slenderness ratio; the pile length has more influence on increasing the lateral deflection. Furthermore, the lateral deflections versus depth along pile length at the same slenderness ratio revealed that the piles with bigger diameters exhibited less lateral deflections, which might be attributed to the increase in the surface area and hence the skin friction between pile and soil. Keywords: Finite Element Method, Lateral deflection, Single Pile, Slenderness Ratio, Ricker Wavelet. ………………………………………………………………………………………………………………………… ÖZ:Bu tez çalışmasında 3D nonlinear statik ve dinamik analiz yöntemleri ile yanal yükler altında kazık temelin narinlik katsayısının (L/D) yanal deplasmanlara etkisi çalışılmıştır. Farklı kazık, zemin ve yükler modellenmiş ve bunların yanal harekete etkisi irdelenmiştir. Zemin elastik, elastoplastik ve dinamik modellerle simüle edilmiştir. Sismik etkiyi yaratabilmek içinse, sismik modellemede sıklıkla kullanılan ve band-sınırlı bir frekans içeriği olan Ricker dalgacığı kullanılmıştır. 3D modelleme sonlu elemanlar yöntemi ile ABAQUS yazılımı kullanılarak değerlendirilmiştir. Sonuç olarak yanal deplasmanlar üzerinde en büyük unsurun narinlik katsayısı olduğu ve bu katsayı sabit tutulup kazık boyu ve çapı değiştirildiği zaman, boyunun artmasının yanal deplasmanları artırırken, çapının artmasının ise yanal deplasmanları düşürdüğü gözlemlenmiştir. Ayrıca, çapın artması ile kazık yüzey alanının arttığı ve dolayısıyla sürtünme direncinin de artmasından dolayı yanal deplasmanlarda azalma olduğu sonucuna varılmıştır. Keywords: Sonlu elemanlar yöntemi, Yanal deplasman, Tek kazık, Narinlik katsayısı, Ricker dalgacığı.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2012. Supervisor: Assist. Prof. Dr. Huriye Bilsel.
Keywords: Civil Engineering; Structural Dynamics; Finite Element Method Lateral Deflection Single Pile Slenderness Ratio Ricker Wavelet